Utilization of Hybrid Digital Technologies for Optimizing Waste Bank Management and Elevating Community Literacy - Imam Saputra; Mesran Mesran; Dian Purnama Sari; Dito Putro Utomo (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
Grassroots community waste banks play a pivotal role in urban environmental management; however, they frequently face operational bottlenecks due to reliance on conventional paper-based record-keeping. The community partner faced severe challenges, including administrative processing delays, accounting errors in customer balances, and limited market reach for upcycled products. To address these problems, this community service activity aimed to optimize waste bank administration and elevate digital marketing literacy through an integrated hybrid capacity-building framework. The contribution of this initiative lay in deploying a low-latency hybrid learning setup—combining dual-WAN bonding, multi-camera switching, and cloud-accessible digital ledger tools—to deliver interactive training across physical and synchronous online cohorts (). Methodologically, a mixed-methods approach evaluated participant progress using pre- and post-test diagnostic questionnaires and post-event usability surveys. The results of the community service demonstrated a statistically significant increase in participant digital literacy (), with composite cognitive scores improving from a baseline of to , achieving a high normalized Hake gain (). Field execution successfully digitized operational transaction logs, eliminated calculation discrepancies, and enabled digital cataloging on social media platforms for waste-derived products. Overall participant evaluation indicated outstanding satisfaction (), confirming the practical utility and technical reliability of the hybrid delivery system. This activity successfully transformed the partner's operational workflows from manual ledgers to transparent digital management while offering a scalable model for circular economy empowerment.